Global Sea Ice Concentration (netCDF) - DMSP ... : OSI-401-b ... - OSI SAF; EUMETSAT SAF On Ocean And Sea Ice (EUMETSAT SAF on Ocean and Sea Ice, 2017)
Daily averaged fractional ice cover in percentage, processed from passive microwave satellite data (SSMIS) over the polar regions. Sea ice concentration and its uncertainties are calculated from swath observations, and averaged and gridded to the daily fields. Better than using this archived NRT sea ice concentration product, please use the reprocessed sea ice concentration data record v2.0 (EO:EUM:DAT:MULT:OSI-450). ...